1958
DOI: 10.1111/j.1365-2621.1958.tb17606.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CERTAIN CHEMICALS IN WATER ON THE FLAVOR OF BREWED COFFEEa

Abstract: Organoleptic studies of odor-producing impurities which might impair the taste of water supplies and coffee brewed therefrom have been conducted and taste thresholds of six odor-producing chemicals and four non-volatile compounds used in water treatment have been estimated. These experiments supplement earlier work by Lockhart, Tucker, and Merritt (2) which was concerned with threshold levels of inorganic ions normally present in water supplies.Ammonia, chlorine, hydrogen sulfide, phenol and the ortho-and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…the present study with those reported by others is diffi cult because of gross differences in methodology, testing conditions, and criteria for threshold definition. Campbell et al 6 reported a taste threshold for chlorine residual of 5.2 mg/1 in redistilled water, using the triangle test method and the chlorine concentration related to 50 per cent above chance correct response as the threshold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the present study with those reported by others is diffi cult because of gross differences in methodology, testing conditions, and criteria for threshold definition. Campbell et al 6 reported a taste threshold for chlorine residual of 5.2 mg/1 in redistilled water, using the triangle test method and the chlorine concentration related to 50 per cent above chance correct response as the threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Campbell et al 6 reported the taste threshold of chlorine in redistilled water as 5.2 ppm. In their re view, McKee and Wolf7 credit Um-benhauer8 with the statement that objectionable tastes and odors were not produced with residual chlorine concentrations as high as 2.0 ppm.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia is another important parameter usually monitored in routine wastewater treatment. Ammonia in water can be tasted at levels of about 34 ppm (Campbell et al 1958). The presence of elevated ammonia levels in raw water can result in moldy, earthy-tasting water that may interfere with the operation of manganese-removal filters (Dieter and Möller 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The threshold of odor in domestic water supplies is 5 mgj£ (t~cKee and Wolf 1971). Humans can taste NH 3 in coffee at 35 mg/t (Campbell et al 1958). Concentrations >40 mg/£ were acutely toxic to aquatic plants (Klussman et al 1970).…”
Section: Concentrations Of Nhmentioning
confidence: 99%